2017
DOI: 10.4172/2168-9881.1000167
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Pasting Properties High Quality Cassava Flour (HQCF) and Wheat Flour Blends

Abstract: High quality cassava flour (HQCF) processed from five different improved cassava varieties (TMS87164, NR8082, TME419, TMS0581 and TMS98/1632) were evaluated for their physicochemical, functional and pasting properties to determine their suitability for baked goods. The HQCFs were then blended with wheat flour (WF) at various ratios (0:100, 10:90, 20:80, 30:70, 40:60 and 50:50% HQCF:WF respectively) and analyzed for the various parameters. The results showed significantly (p<00.05) low contents of moisture, ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…It is, therefore, likely that similar modification took place in cassava starch in this study, since cassava starches have been reported to exhibit even lower onset gelatinization temperature than corn starches (Elgadir et al, 2009). The packed bulk density (0.62 g/mL) obtained for native HQCF in this study is within the range (0.55 to 0.77 g/mL) previously reported by Iwe et al (2017) for HQCFs produced from five different cassava varieties. Bulk density of flour has been noted to influence the development of dough when reconstituted with water (Udoro, Kehinde, Olasunkanmi, & Charles, 2014).…”
Section: Integrated Food Sciencesupporting
confidence: 84%
See 2 more Smart Citations
“…It is, therefore, likely that similar modification took place in cassava starch in this study, since cassava starches have been reported to exhibit even lower onset gelatinization temperature than corn starches (Elgadir et al, 2009). The packed bulk density (0.62 g/mL) obtained for native HQCF in this study is within the range (0.55 to 0.77 g/mL) previously reported by Iwe et al (2017) for HQCFs produced from five different cassava varieties. Bulk density of flour has been noted to influence the development of dough when reconstituted with water (Udoro, Kehinde, Olasunkanmi, & Charles, 2014).…”
Section: Integrated Food Sciencesupporting
confidence: 84%
“…Higher starch contents were found in flours from three cassava varieties studied than wheat flours by Eriksson, Koch, Tortoe, Akonor, and Baidoo (2014). Similarly, Iwe et al (2017) recently attributed higher carbohydrate and lower protein contents for the higher WAC of HQCF than that of wheat flour. Higher amylopectin contents in cassava than in wheat has also been reported to be responsible for their higher WAC (Eriksson et al, 2014).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…For composite flours to be applied in the production of food systems, a foreknowledge of their performance is required [15] as Improper knowledge of these functionalities have resulted in products with varying consumer acceptability [15]. Functional properties are fundamental physicochemical properties which reflect how food ingredients behave during preparation and cooking.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, accession UG120156 had the lowest breakdown viscosity while accession UG120198 was the highest, implying that accession UG120198 had the most stable paste. Accessions with high breakdown viscosity have critical usability and process-ability characteristics as has been obeserved in cassava [9] and other flour sources [15][16] [17] making them important for use where stable pastes are required. In this study, final viscosity ranged from 3000cP to 3500cP with clear differences between most of the accessions.…”
Section: Pasting Properties Of Cassava Flourmentioning
confidence: 99%